Odpowiedzi

2010-01-18T13:42:10+01:00
1)
L=tgxctgx+tgx-ctgx-1=1-1+tgx-ctgx=tgx-ctgx=P
2)
L=tgx*ctgX+1=1+1=2=2*1=2*(sin^2x+cos^2x)=P
wzory tgx*ctgx=1
sin^2x+cos^2x=1 - jedynka tryg
Najlepsza Odpowiedź!
2010-01-18T13:44:32+01:00
(tgα-1)(ctgα+1)=tgα-ctgα
L=(tgα-1)(ctgα+1)=tgα*ctgα-tgα-ctgα-1=
1 + tgα-ctgα-1=1+tgα-ctgα-1= tgα-ctgα=P
lub
L=(tgα-1)(ctgα+1)=tgα*ctgα-tgα-ctgα-1=
sinα/cosα* cosα/sinα + tgα-ctgα-1=1+tgα-ctgα-1= tgα-ctgα=P

tgα*ctgα+1=2(sin²α+cos²α)
L=tgα*ctgα+1=sinα/cosα *cosα/sinα+1=1+1=2
lub
L=tgα*ctgα+1=1+1=2
P=2(sin²α+cos²α)=2*1=2

L=P

Korzystamy z podstawowych tożsamości trygonometrycznych:
1. sin²α+cos²α=1
2. tgα= sinα/cosα
3.ctgα=cosα/sinα
4. tgα*ctgα=1
2010-01-18T13:51:40+01:00